Model Kredibilitas Bühlmann-Straub untuk Frekuensi Klaim Berdistribusi Binomial Negatif–Lindley - Ikhsan Maulidi; Rini Oktavia; Uswah; Alim Misbullah; Vina Apriliani (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
The credibility theory is one of the tools that can be used to determine risk-based premiums. One approach that can be used is the best accuracy approach such as Bühlmann-Straub. We study the parametric Bühlmann-Straub credibility model in which the claim frequency data is assumed to follow the Negative-Lindley (NB-L) Binomial distribution. Determination of the Bühlmann-Straub parameter is determined by using the basic rules in probability theory. From the study that has been carried out, an explicit equation has been obtained to determine the credibility premium of Bühlmann-Straub. A simulation of the application of the model to the data was also provided by assuming the data follows the NB-L distribution. The NB-L distribution parameters were estimated using the momen method and maximum likelihood estimation. From the simulation, it is found that the data used had a high credibility factor value which implies the data can be considered primely for estimating future premiums.